Efektivitas Penggunaan Layanan Digital Banking connect Dalam Merespon Kebutuhan Nasabah (Studi pada Bank Jatim Cabang Kediri ) - Danang Suhiryo; Ahsin Daroini (Otonomi, 2023)
The purpose of this study was to determine the implementation of digital Banking Jconnect at Bank Jatim Kediri Branch. Supporting and inhibiting factors in the effective use of Jconnect digital banking services at Bank Jatim Kediri branch. The Systematic Literature Review method is used to find answers to these research questions by searching for studies that use digital Jconnect online banking services and conducting narrative synthesis of these findings. The level of effectiveness of the Jconnect service system is known from indicators of customer understanding, right on target, on time, achieving goals and real changes.